Low Cost and Precise Jitter Measurement Method for TRNG Entropy Assessment - Florent Bernard; Arturo Garay; Patrick Haddad; Nathalie Bochard; Viktor Fischer (Transactions on Cryptographic Hardware and Embedded Systems, 2023)
Random number generators and specifically true random number generators (TRNGs) are essential in cryptography. TRNGs implemented in logic devices usually exploit the time instability of clock signals generated in freely running oscillators as source of randomness. To assess the performance and quality of oscillator-based TRNGs, accurate measurement of clock jitter originating from thermal noise is of paramount importance. We propose a novel jitter measurement method, in which the required jitter accumulation time can be reduced to around 100 reference clock periods. Reduction of the jitter accumulation time reduces the impact of the flicker noise on the measured jitter and increases the precision of the estimated contribution of thermal noise. In addition, the method can be easily embedded in logic devices. The fact that the jitter measurement can be placed in the same device as the TRNG is important since it can be used as a basis for efficient embedded statistical tests. In contrast to other methods, we propose a thorough theoretical analysis of the measurement error. This makes it possible to tune the parameters of the method to guarantee a relative error smaller than 12% even in the worst cases.